2017
DOI: 10.3390/cells6040047
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Control for Detection of Functional CD4 T Cells in PBMC: The CPI Pool

Abstract: Testing of peripheral blood mononuclear cells (PBMC) for immune monitoring purposes requires verification of their functionality. This is of particular concern when the PBMC have been shipped or stored for prolonged periods of time. While the CEF (Cytomegalo-, Epstein-Barr and Flu-virus) peptide pool has become the gold standard for testing CD8 cell functionality, a positive control for CD4 cells is so far lacking. The latter ideally consists of proteins so as to control for the functionality of the antigen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Several studies have suggested that influenza virus is able to directly infect B cells and T cells [44, 45]. In our study, IFA results indicated that influenza virus could effectively infect PBMCs in vitro , which was in accordance with the previous studies [46, 47] and laid a foundation for ensuing experiments. The results of in vitro infection experiments suggested that compared with mock-infected cells, the frequencies of these two groups of cells and IL-17A levels were reduced at all assessed time points postinfection with H7N9, substantiating the findings for acute-phase H7N9 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have suggested that influenza virus is able to directly infect B cells and T cells [44, 45]. In our study, IFA results indicated that influenza virus could effectively infect PBMCs in vitro , which was in accordance with the previous studies [46, 47] and laid a foundation for ensuing experiments. The results of in vitro infection experiments suggested that compared with mock-infected cells, the frequencies of these two groups of cells and IL-17A levels were reduced at all assessed time points postinfection with H7N9, substantiating the findings for acute-phase H7N9 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Stimulation of all six HCMV-seronegative donors with each of the twenty HCMV peptide pools failed to elicit an increased number of IFN-γ-producing T cells relative to PBMC cultured in media alone (Table 1). However, each of these HCMV-seronegative donor PBMC robustly responded to a combination of cytomegalovirus (C), parainfluenza (P), and influenza (I) antigens, collectively referred to as CPI (20), which confirmed T cell functionality in the respective samples (Table 1). The inability to detect a recall response to the HCMV peptide pools in HCMV-seronegative donors, in the face of their CPI reactivity, establishes the exquisite specificity of the HCMV peptide pool-triggered recall responses.…”
Section: Resultsmentioning
confidence: 76%
“…HCMV and EBV grade 2 antigens (UV-inactivated virions) were purchased from Microbix (Mississauga, Ontario, Canada) and tested at a final concentration of 30 μg/mL. CPI (from CTL) was used as a positive control in all experiments because unlike CEF peptides, CPI elicits T cell recall responses in all healthy donors (20). CEF is a pool of 32 immune dominant nonamer peptides derived from CMV, EBV and the influenza virus commonly used as a positive control for CD8+ T cell recall (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While HCMVpp65 is thought to be an immune-dominant antigen of the virus [ 14 , 49 ], it is not its only immunogenic antigen. Actually, by testing peptide pools that cover 20 open reading frames of HCMV, we found that most of them were targeted by T cells, and that the pp65 protein was only one of those recognized [ 50 ]. Thus, it is possible that I-HCMV-positive but HCMVpp65-negative individuals responded to other HCMV antigens than HCMVpp65.…”
Section: Discussionmentioning
confidence: 99%